Fenomena Pengemis Anak di Kota Kendari - La Taslim; Wa Ode Sifatu (JURNAL KABANTI: Kerabat Antropologi, 2023)
The purpose of this research is to describe the children of beggars in Kendari City, and to find out and describe the causes of children becoming beggars in Kendari City. The theory used in this study is Oscar Lewi's (1988) cultural theory, that poverty that occurs in society is not solely due to the economy, but rather the existence of deficiencies in one's culture and psychology so as to form a culture that is passed down from generation to generation through socialization.The method used in this qualitative descriptive research is trying to reveal why there are still many child beggars in Kendari City who take to the streets to beg, and how child beggars socialize with their families and neighbors. Data collection techniques were carried out in several ways, namely by using observation methods and in-depth interviews which aim to obtain accurate data, observation of participation by observing child beggars and their relationships with other beggars and their families. Based on the research results obtained in this study, the factors that cause the existence of these child beggars are parents' income that is not sufficient to meet their needs, jobs that are easy to do and strategic location selection. In addition, there is family socialization and peer socialization.